2009
DOI: 10.1103/physreve.79.051124
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution of product shock measures in the totally asymmetric simple exclusion process with sublattice-parallel update

Abstract: It is known that when the steady state of a one-dimensional multispecies system, which evolves via a random-sequential updating mechanism, is written in terms of a linear combination of Bernoulli shock measures with random-walk dynamics, it can be equivalently expressed as a matrix-product state. In this case the quadratic algebra of the system always has a two-dimensional matrix representation. Our investigations show that this equivalence exists at least for the systems with deterministic sublattice-parallel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 11 publications
0
32
1
Order By: Relevance
“…It is shown that this steadystate can be also written in terms of a product of four non-commuting matrices. One of the main results obtained here is that these matrices have exactly the same generic structure of the matrices first introduced in [7] indicating that the steady-state of a onedimensional driven-diffusive system can be written as a linear superposition of product shock measures. It is easy now to explain the two-dimensional matrix representation of the PASEP with parallel dynamics introduced in [8,9].…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…It is shown that this steadystate can be also written in terms of a product of four non-commuting matrices. One of the main results obtained here is that these matrices have exactly the same generic structure of the matrices first introduced in [7] indicating that the steady-state of a onedimensional driven-diffusive system can be written as a linear superposition of product shock measures. It is easy now to explain the two-dimensional matrix representation of the PASEP with parallel dynamics introduced in [8,9].…”
mentioning
confidence: 56%
“…The matrices L and R are also written in the basis (0, 1). Following [7] let us define two different product shock measures. We denote the shocks at even sites 2k (k = 1, · · · , L) as |µ 2k and at odd sites 2k + 1 (k = 0, · · · , L) as |µ 2k+1 respectively:…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Three families of two-state systems with nearest-neighbor interactions have been introduced and studied in [5]. This has been also generalized to the multi-species systems with long range interactions and even the systems with discrete time updating scheme [10]. The study of the steady-state properties of onedimensional driven-diffusive systems has a long history.…”
Section: Introductionmentioning
confidence: 99%